Evaluation of audit fees of farmed out accounts by the AGes Office in Singapore : a regression analysis approach - School of Accountancy and Business (2008)
The AGes Office had been working on an audit fees regression model to predict the audit fees of statutory boards. This report is based on discussions with the AGes Office and results of prior studies on the prediction of audit fees. A list of 13 potential audit fees determinants is identified. Audit fees determinants relate to the audit risk and the amount of audit work in a statutory board audit.